2019
DOI: 10.1016/j.jconrel.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating accessibility of intravenously administered nanoparticles at the lesion site in rat and pig contusion models of spinal cord injury

Abstract: In spinal cord injury (SCI), timely therapeutic intervention is critical to inhibit the post-injury rapidly progressing degeneration of spinal cord. Towards that objective, we determined the accessibility of intravenously administered biodegradable nanoparticles (NPs) as a drug delivery system to the lesion site in rat and pig contusion models of SCI. Poly (D,L-lactide co-glycolide, PLGA)-based NPs loaded with a near-infrared dye as a marker for NPs were used. To analyze and quantify localization of NPs to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…In a rat reperfusion injury model, PLGA NPs loaded with both catalase and SOD mitigated the inflammatory response, prevented apoptosis of neuronal cells, and protected the blood brain barrier from ROS-mediated reperfusion injury as compared to blank NPs (10). Intravenous administration to rat and pig models of SCI found a dose-dependent localization of NPs to the site of injury, and in rats, the NPs could be detected at the site of epicenter even at 4 weeks post-injury (33). The dose for our study (6 mg/kg) was determined based on these previous publications.…”
Section: Discussionmentioning
confidence: 94%
“…In a rat reperfusion injury model, PLGA NPs loaded with both catalase and SOD mitigated the inflammatory response, prevented apoptosis of neuronal cells, and protected the blood brain barrier from ROS-mediated reperfusion injury as compared to blank NPs (10). Intravenous administration to rat and pig models of SCI found a dose-dependent localization of NPs to the site of injury, and in rats, the NPs could be detected at the site of epicenter even at 4 weeks post-injury (33). The dose for our study (6 mg/kg) was determined based on these previous publications.…”
Section: Discussionmentioning
confidence: 94%
“…These events, together with factors conferring neuronal susceptibility, likely produced cell death close to the injury site. Adult minipigs weight only between 20 and 85 kg depending on the species, 78 and therefore are gaining ground against domestic pigs as experimental model in SCI 37,39,[42][43][44][45][46][47][78][79][80] and other biomedical research fields. 78 There is no doubt that adult pigs of manageable weight will be preferable to domestic piglets for SCI research unless the objectives of the study specifically relate to pediatric injuries.…”
Section: Kinematics Of Locomotionmentioning
confidence: 99%
“…Despite the translational advantages of research data gathered in swine, the use of this model in the SCI field has not yet consolidated. Most studies using pigs deal with thoracic SCI, 37,39,[42][43][44][45][46][47][48][49] whereas a few have produced cervical sevoflurane (1.7 % -2 %) together with remifentanil (26 mg/kg/h IV) and rocuronium (1.2 mg/kg/h IV). Mechanical ventilation (Fabius Tiro, DrĂ€ger) was set at 12-14 breaths/min with a tidal volume of 10-15 ml/kg.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that ROS scavenging can suppress the inflammation in secondary injury following TSCI. 21 , 44 Therefore, we investigated the in vivo anti-inflammatory properties of the Se-CQDs at 5 days post operation. The immunostaining of the spinal cord showed an increase in the numbers of cells positive for CD68 (a marker of microglia) in the lesion sites of rats from the saline treatment group.…”
Section: Resultsmentioning
confidence: 99%